The Role of Strategic Thinking in Building Organizational Ambidexterity: Applied Study on the Public Shareholding Companies Listed in Amman Stock Exchange - Abuzaid, Ahmad (Jordan Journal of Business Administration, 2019)
The primary purpose of this study was to test the effect of strategic thinking on organizational ambidexterity in the public shareholding companies listed in Amman Stock Exchange. A questionnaire that targeted (150) respondents resulted in (139) usable questionnaire forms with a response rate of 92.7 percent. Multiple linear regression was used to examine the study hypotheses. The study found that public shareholding companies apply strategic thinking at a moderate level, where the arithmetic mean was (3.25) and revealed a moderate level of organizational ambidexterity, where the arithmetic mean was (3.57). Additionally, the study found a positive and statistically significant impact for strategic thinking on organizational ambidexterity and its dimensions; namely, exploitation and exploration. Based on these findings, the study recommends adopting strategic thinking in strategic planning processes and implementing strategies because of their importance in improving the competitive position, developing the capacities of managers at different levels in the field of strategic thinking through training, seminars and workshops, providing the necessary requirements to facilitate the process of strategic thinking, such as developing organizational culture supportive of strategic thinking, adopting a clear vision, encouraging processes of innovation and creativity and following a holistic and systemic thinking approach to deal with the future, striving towards achieving organizational ambidexterity through strategic thinking and by adopting other methods due to the importance of organizational ambidexterity in enhancing the performance of organizations and maintaining their long-term sustainability.